Polycyclic aromatic hydrocarbons (PAHs) removal by sorption: A review - Sarukkalige, Priyantha; Lamichhane, S.; Bal Krishna, K. (Pergamon Press, 2016)
Polycyclic aromatic hydrocarbons (PAHs) are organic micro pollutants which are persistent compounds in the environment due to their hydrophobic nature. Concerns over their adverse effects in human health and environment have resulted in extensive studies on various types of PAHs removal methods. Sorption is one of the widely used methods as PAHs possess a great sorptive ability into the solid media and their low aqueous solubility property. Several adsorbent media such as activated carbon, biochar, modified clay minerals have been largely used to remove PAHs from aqueous solution and to immobilise PAHs in the contaminated soils. According to the past studies, very high removal efficiency could be achieved using the adsorbents such as removal efficiency of activated carbon, biochar and modified clay mineral were 100%, 98.6% and >99%, respectively. PAHs removal efficiency or adsorption/absorption capacity largely depends on several parameters such as particle size of the adsorbent, pH, temperature, solubility, salinity including the production process of adsorbents. Although many studies have been carried out to remove PAHs using the sorption process, the findings have not been consolidated which potentially hinder to get the correct information for future study and to design the sorption method to remove PAHs. Therefore, this paper summarized the adsorbent media which have been used to remove PAHs especially from aqueous solutions including the factor affecting the sorption process reported in 142 literature published between 1934 and 2015.